Membongkar Tabir Perselingkuhan: Perspektif Hadis Abu Daud No.1692 Dan KUHP 284 - Maharani, Siti; Arifin, Tajul (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Extramarital affairs are becoming an increasingly prevalent social phenomenon in the modern era. This research aims to examine the understanding and definition of extramarital affairs in Islam, the concept of extramarital affairs based on Hadith Abu Dawood No. 1692, the sanctions and punishments for the perpetrators, preventive measures for extramarital affairs from an Islamic legal perspective, and its correlation with the provisions of adultery in the Criminal Code of Indonesia (KUHP) Article 284. A qualitative method with a text and content analysis approach is used to conduct this research, as well as a literature study. The research results show that extramarital affairs in Islam are categorized as a major sin that has the potential to damage the harmony of families and society. Hadith Abu Dawood No. 1692 emphasizes the prohibition of extramarital affairs and provides an overview of the sanctions for the perpetrators. Preventive measures for extramarital affairs in Islam include fostering faith and morality, strengthening families, and providing sexual education. The Criminal Code of Indonesia (KUHP) Article 284 regulates adultery with criminal sanctions, but its relevance as a sanction for perpetrators of extramarital affairs still needs to be studied further. This research concludes that Islamic law plays an important role in preventing and addressing extramarital affairs, and its integration with positive law needs to be considered to realize justice and the common good.